1997
DOI: 10.1074/jbc.272.50.31225
|View full text |Cite
|
Sign up to set email alerts
|

Correlating Ca2+ Responses and Secretion in Individual RBL-2H3 Mucosal Mast Cells

Abstract: The role of Ca 2؉ in stimulus-response coupling in nonexcitable cells is still not well understood. The Ca 2؉ responses of individual cells are extremely diverse, often displaying marked oscillations, and almost nothing is known about the specific features of these Ca 2؉ signals that are important for the functional response of a cell. Using the RBL-2H3 mucosal mast cell as a model, we have studied the temporal relationship between changes in intracellular Ca 2؉ and serotonin secretion at the single-cell level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
69
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 42 publications
8
69
0
1
Order By: Relevance
“…Previous studies have demonstrated that activation of PKC and elevation of intracellular Ca 2ϩ are sufficient and necessary for the release of these inflammatory mediators from granules (85)(86)(87). By contrast, studies have shown that the MAPKs are not required for the release of these inflammatory mediators, but are involved in the production of arachidonic acid and cytokines (27,33,88).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that activation of PKC and elevation of intracellular Ca 2ϩ are sufficient and necessary for the release of these inflammatory mediators from granules (85)(86)(87). By contrast, studies have shown that the MAPKs are not required for the release of these inflammatory mediators, but are involved in the production of arachidonic acid and cytokines (27,33,88).…”
Section: Discussionmentioning
confidence: 99%
“…This premise is in line with the notion that receptor-stimulated tyrosine kinase cascades that lead to the translocation and activation of PI3K of PLC␥ bear a high degree of similarity in the signaling mechanism among these cell types. Ca 2ϩ signaling in response to Fc⑀RI cross-linking is essential to the antigen-induced secretion of inflammatory mediators in RBL-2H3 cells (31,46), and therefore is one of the key early events in mast-cell signal transduction. The present data support our hypothesis that PI3K and PLC␥ play a concerted role in initiating antigen-induced Ca 2ϩ signaling (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In the rat basophilic leukemia (RBL)-1 mast cell line, stimulation of the G protein-coupled cysteinyl leukotriene type I (cysLT1) receptor with low concentrations of the agonist LTC 4 evokes a series of cytoplasmic Ca 2+ oscillations (7), typical of the large all-or-nothing baseline Ca 2+ spikes seen in many other cell types. By contrast, activation of FCεRI receptors with antigen or IgE leads to a Ca 2+ response that develops after a longer delay and which is punctuated by a series of slow Ca 2+ oscillations on an elevated background Ca 2+ rise (15,16). Both types of Ca 2+ response depend on Ca 2+ influx through CRAC channels: Both agonists activate CRAC channels in RBL cells (16,17), and exposure to CRAC channel blockers accelerates decline of the Ca 2+ signal in response to either cysLT1 (7) or FCεRI receptor activation (18).…”
mentioning
confidence: 99%